Plasma Proteome Profiling to detect and avoid sample‐related biases in biomarker studies. Issue 11 (30th September 2019) - Geyer, Philipp E; Voytik, Eugenia; Treit, Peter V; Doll, Sophia; Kleinhempel, Alisa; Niu, Lili; Müller, Johannes B; Buchholtz, Marie‐Luise; Bader, Jakob M; Teupser, Daniel; Holdt, Lesca M; Mann, Matthias
Abstract: Plasma and serum are rich sources of information regarding an individual's health state, and protein tests inform medical decision making. Despite major investments, few new biomarkers have reached the clinic. Mass spectrometry (MS)‐based proteomics now allows highly specific and quantitative readout of the plasma proteome. Here, we employ Plasma Proteome Profiling to define quality marker panels to assess plasma samples and the likelihood that suggested biomarkers are instead artifacts related to sample handling and processing. We acquire deep reference proteomes of erythrocytes, platelets, plasma, and whole blood of 20 individuals (> 6, 000 proteins), and compare serum and plasma proteomes. Based on spike‐in experiments, we determine sample quality‐associated proteins, many of which have been reported as biomarker candidates as revealed by a comprehensive literature survey. We provide sample preparation guidelines and an online resource ( www.plasmaproteomeprofiling.org ) to assess overall sample‐related bias in clinical studies and to prevent costly miss‐assignment of biomarker candidates. Synopsis: This study describes marker panels for the systematic assessment of plasma samples that report on erythrocyte lysis, platelet contamination and coagulation. Marker panels can assess entire clinical studies or individual samples for quality issues and allow evaluation of biomarker candidates. Deep reference proteome data (> 6, 000 proteins) from erythrocytes, platelets, platelet‐rich plasma, platelet‐free plasma and whole blood from 20 individuals, distilled in three quality marker panels of 30 proteins each. The influence of blood sampling equipment and sample processing protocols on the plasma proteome is compared. The www.plasmaproteomeprofiling.org website allows the automated quality assessment of single samples and clinical studies. A general guideline for minimizing pre‐analytical variations in future clinical studies is proposed. Evaluation of 210 biomarker studies reveal that about 50% of them report proteins of the quality marker panels, indicating potential sample handling issues. Abstract : This study describes marker panels for the systematic assessment of plasma samples that report on erythrocyte lysis, platelet contamination and coagulation. Marker panels can assess entire clinical studies or individual samples for quality issues and allow evaluation of biomarker candidates.